Predicting the Effects of CYP2C19 and Carboxylesterases on Vicagrel, a Novel P2Y12 Antagonist, by Physiologically Based Pharmacokinetic/Pharmacodynamic Modeling Approach - Liu, Shuaibing; Wang, Ziteng; Tian, Xin; Cai, Weimin (Frontiers in Pharmacology, 2020)
Vicagrel, a novel acetate derivative of clopidogrel, exhibits a favorable safety profile and excellent antiplatelet activity. Studies aim at identifying genetic and non-genetic factors affecting vicagrel metabolic enzymes CYP2C19, CES1 and CES2, which may potentially lead to altered pharmacokinetics and pharmacodynamics, are warranted. A physiologically based pharmacokinetic/pharmacodynamic (PBPK/PD) model incorporating vicagrel and its metabolites was constructed, verified and validated in our study, which could simultaneously characterize its sequential two step metabolism and clinical response. Simulations were then performed to evaluate the effects of CYP2C19, CES1 and CES2 genetic polymorphisms as well as inhibitors of these enzymes on vicagrel pharmacokinetics and antiplatelet effects. Results suggested vicagrel was less influenced by CYP2C19 metabolic phenotypes and CES1 428 G>A variation, in comparison to clopidogrel. No pharmacokinetic difference in the active metabolite was also noted for volunteers carrying different CES2 genotypes. Omeprazole, a CYP2C19 inhibitor, and simvastatin, a CES1 and CES2 inhibitor, showed weak impact on the pharmacokinetics and pharmacodynamics of vicagrel. This is the first study proposing a dynamic PBPK/PD model of vicagrel able to capture its pharmacokinetic and pharmacodynamic profiles simultaneously. Simulations indicated that genetic polymorphisms and drug-drug interactions showed no clinical relevance for vicagrel, suggesting its potential advantages over clopidogrel for treatment of cardiovascular diseases. Our model can be utilized to support further clinical trial design aiming at exploring the effects of genetic polymorphisms and drug-drug interactions on PK and PD of this novel antiplatelet agent.